Risk preference during collective decision making: ant colonies make risk-indifferent collective choices. (October 2017) - Hübner, Carolin; Czaczkes, Tomer J.
Abstract : The study of how animals respond to risk has had a strong influence on our understanding of animal behaviour. By risk, we refer to a situation where organisms must exploit a resource with an unstable quality. Animals may have different risk preferences: they may be risk seeking (e.g. prefer a gamble of 2 or 4 versus a safe bet of 3), risk averse or risk insensitive. Among invertebrates, bees are the most studied group in terms of risk preference. However, in eusocial insects such as bees and ants, the unit of selection is the colony. Thus, the risk preference of eusocial animals is best understood at the level of the group. More broadly, many group-living animals must make consensus decisions between options with varying risk. However, to our knowledge no study has yet set out to examine risk preference during collective decision making by groups. This study aimed to address this gap. Colonies of the ant Lasius niger were given access to two feeders, one offering a fixed 0.55 M sucrose solution and the other alternating every 3 min between 0.1 M and 1.0 M. Colonies almost always (26/28 trials) made a collective decision. While there was a small tendency for the variable feeder to be chosen if it initially offered 1 M sucrose, broadly speaking the fixed or variable feeders were equally likely to be chosen. Ant colonies thus showed risk neutrality during collective foraging decisions. Unexpectedly, and contrary to the classical understanding of pheromone-based collective decision making, the choice of feeder was only very weakly influenced by the initial quality of the variable feeder. We propose that risk preference during collective decision making by groups is a woefully understudied topic, and worthy of future work in both recruitment-based and nonrecruiting decision-making systems. Highlights: Risk preference and collective decision making have both been well studied. To date, no explicit test of collective risk preference has been made. We address this gap by studying the foraging risk preference of ant colonies. Lasius niger colonies consistently make consensus decisions, but are risk indifferent. Behaviour of groups cannot be fully predicted by that of the constituent parts.